2019
DOI: 10.1136/sextrans-2019-054098
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and utility-based quality of life impact of screening test results for anal precancerous lesions in gay and bisexual men: baseline findings from the Study of the Prevention of Anal Cancer

Abstract: ObjectiveGay, bisexual and other men who have sex with men (GBMSM), particularly HIV-positive GBMSM, are at increased anal cancer risk compared with the general population. This study examined the psychological and quality of life (QoL) impact of receiving abnormal anal cancer screening results during the baseline visit of the Study of the Prevention of Anal Cancer (SPANC).MethodsSPANC was a prospective cohort study of the natural history of anal human papillomavirus (HPV) and associated abnormalities in GBM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…In some studies, respondents were also asked to rate their own health on the EQ-5D visual analog scale, ranging from 0 (worst imaginable health status) to 100 (best imaginable health status) [72][73][74] as well. Additionally, two studies reported Short-Form Six-Dimension (SF-6D) utility scores, which were either derived from the SF-36 using the UK scoring algorithm [67], or the SF-12 using the University of Sheffield's SF-6D classification for describing health [50]. The SF-6D estimates a preference-based single index measure for health using general population values, and allows utility scores to be obtained with scores covering a range of 0 (worst health state) to 1 (best health state) [40,53].…”
Section: Measures Of and Results For Other Functional Status And Well...mentioning
confidence: 99%
“…In some studies, respondents were also asked to rate their own health on the EQ-5D visual analog scale, ranging from 0 (worst imaginable health status) to 100 (best imaginable health status) [72][73][74] as well. Additionally, two studies reported Short-Form Six-Dimension (SF-6D) utility scores, which were either derived from the SF-36 using the UK scoring algorithm [67], or the SF-12 using the University of Sheffield's SF-6D classification for describing health [50]. The SF-6D estimates a preference-based single index measure for health using general population values, and allows utility scores to be obtained with scores covering a range of 0 (worst health state) to 1 (best health state) [40,53].…”
Section: Measures Of and Results For Other Functional Status And Well...mentioning
confidence: 99%
“…Es deber del profesional de salud orientar a la persona, clara y objetivamente, sobre la transmisión y tratamiento de la enfermedad. 31,32 Cumple considerar, aún, que la presencia de verrugas genitales actúa como "marcador" de ITS, ya que se estima que 20% de las personas con verrugas anogenitales tengan una ITS simultánea, incluyendo clamidia, infección por VIH y sífilis. Por lo tanto, el rastreo de otras ITS debe ser orientado.…”
Section: Figura 2 -Recomendaciones Para El Tratamiento De Las Verrugaunclassified
“…A prospective cohort analyzed the psychological impact on patients' life quality when they were informed about the tracking exams abnormality in the reference center to prevent anal cancer in Australia. 25 This aforementioned study included as subjects male bisexuals and other men who had sex with males, particularly HIV positives aged 35 or more. The subjects filled a form on global state of health, psychological aspects of their lives at the first consultation and repeated the same questionnaire 2 weeks and 3 months later.…”
Section: Discussionmentioning
confidence: 99%
“…After getting the results of the tracking exams, patients that were positive showed significantly lower scores when compared to patients that tested negative, mainly when it came to intrusive thoughts and fear of developing cancer. 25 Another study observed life quality in 118 patients of both genders who had anogenital warts using SF-36 and 2 others questionnaires: Skindex-29 and GHO-12. 26 A significant association between the disease quantified by size (>200mm²), the number of anogenital lesions and the lowering of all scores in SF-36 below the average, signifying a worse state of global health, was observed.…”
Section: Discussionmentioning
confidence: 99%